VERIFICATION OF MAGNETOSTRATIGRAPHIC SCALES OF MIOCENE CORE SECTION FROM LAKE BAIKAL - Horiuchi K.; Gol'dberg E.L.; Matsuzaki H.; Kobayashi K.; Shibata Y. (My University, 2004)
The dynamics of cosmogenic 10Be contents in the BDP-96-1 (100 to 200 m) and BDP-98-2 (200 to 600 m) cores was used to test published magnetostratigraphic scales for the Miocene section and to time the core base. Only one of three alternative scales for the BDP-98 core tested against the 10Be decay of T1/2 = 1.5 myr showed a perfect consistency with the decay law. The basal age of the 600 m BDP-98 section was estimted at 8.4 myr.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен